ANALISIS SUKSESI PERUSAHAAN KELUARGA DI KOTA BANDUNG - Rachel Cahyadi (Business Administration Department - Universitas Katolik Parahyangan, 2019)
The Majority of companies in Indonesia are business family. The problem in family business is conflict itself can affect or hinder the process of succession. The goal of this research is to analyse of the preparation of succession can affect the completion of the succession and to knowing about family business barrier in preparation succession on family succession. The population in this research is 59 SMEs Family Business in Bandung. The method that used in this research is quantitative method. The information on this research was collected from disseminate the questionnaire. Interview method is used to confirm each item of the question. The analysis that used in this research is analytic description and Simple linear regression. The result of this research is the preparation of the successor affect the succession of family business succession can increase the impact of family succession preparation on family enterprise success process. from the results of interviews, there are obstacles in the succession process of family companies, namely the difficulty of the next generation is the previous generation still monitoring the running of the business and still in control of making decisions so that the next generation feels constrained and difficult to develop the business.